Case Report: Ultrasound Guided Mucosal Fold Lateralization for Laryngeal Webs - Kanotra, Sohit Paul (Frontiers in Surgery, 2021)
The surgical management of Laryngeal webs is challenging and is associated with a high recurrence rate due the presence of opposing raw mucosal surfaces of the vocal cords, especially near the anterior commissure which causes re-scarring. We describe an endoscopic technique of mucosal flap lateralization (MFL) with ultrasound guidance, which prevents the apposition of the anterior raw surfaces of the vocal cords after web incision, thus avoiding recurrence.